TAKHRIJ HADIS TENTANG KEUTAMAAN DAKWAH HADIST NUR MUHAMMAD SAW - Muhibuddin, Muhibuddin; Farhana, Nurfitria; Al Musawa, Nabiel; Hidayat, Khairul (Moderation | Journal of Islamic Studies Review, 2025)
Muhammad is a teaching about the belief that Allah Swt created the Prophet Muhammad Saw from His Nur, Allah Swt. Since the beginning of Nur Allah was created by Nur Muhammad, this has become the aqidah of the adherents of thariqat or those who practice Sufism in Islam. If the Prophet Muhammad Saw was created from His Nur, so all beings were also created from Nur Muhammad. From His Nur, Allah Swt created Nur Muhammad and from Nur Muhammad, Allah Swt created all creatures. The belief in Nur Muhammad has consequences for the one form, namely the wihdatul form, the unity of the form of Khaliq and the creature, the unity of the form of Allah Swt with the universe. As Al Bushthami said, “I wonder at the one who knows Allah, how can he worship Him?” Also, Al-Bushthami said, “I am holy, I am holy, how great I am.” So whoever has known Allah Wwt, he is the emanation of Allah Wwt so that it sticks to him The divine attributes are Ruubiyah and Uluhiyah. Therefore, how can Allah worship Allah? That is wihdatul as one of the consequences of the teachings about Nur Muhammad.